2000
DOI: 10.1554/0014-3820(2000)054[0704:itieso]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Imitating the Initial Evolutionary Stage of a Tail Ornament

Abstract: Costs of a sexual ornament in its early evolutionary form and the relationship between these costs and individual condition may be an important influence in the likelihood of possible evolutionary mechanisms involved in the evolution of this ornament. We reconstructed the tail shape in hypothetical ancestors of recent hirundines (Aves: Hirundinidae), from which the elongation of tail feathers under sexual selection might have begun. By elongating the tail in sand martins (Riparia riparia, Hirundinidae), we sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 49 publications
(61 reference statements)
1
26
0
Order By: Relevance
“…Few studies have shown that morphological traits preferred by females increase male locomotor costs. One of the few systems in which movement costs of a preferred trait have been extensively considered is tail morphology in birds (Norberg 1994;Møller & Nielsen 1997;Buchanan & Evans 2000;Matyjasiak et al 2000;Park et al 2001). The energetic costs and benefits of elaborate bird tails during flight, however, have not been directly tested; studies thus far have primarily relied on aerodynamic models rather than direct testing of metabolic costs (Rayner 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have shown that morphological traits preferred by females increase male locomotor costs. One of the few systems in which movement costs of a preferred trait have been extensively considered is tail morphology in birds (Norberg 1994;Møller & Nielsen 1997;Buchanan & Evans 2000;Matyjasiak et al 2000;Park et al 2001). The energetic costs and benefits of elaborate bird tails during flight, however, have not been directly tested; studies thus far have primarily relied on aerodynamic models rather than direct testing of metabolic costs (Rayner 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Swords in swordtails can be likened to elaborate tail morphology in birds: one has the potential to affect hydrodynamic aspects of swimming, the other may affect aerodynamic aspects of flight. The initial source of selection favouring elaborate tail morphology in birds has been debated, with some researchers arguing that sexual selection has played the major part (Smith & Montgomerie 1991;Matyjasiak et al 2000), and others maintaining that natural selection arising from aerodynamic benefits plays a strong part in tail evolution (Norberg 1994;Buchanan & Evans 2000;Park et al 2001). For swordtails, phylogenetic information combined with experimental evidence indicates that there was an adaptive field in the form of a female bias favouring a sword when it arose in male swordtails (Basolo 1990b(Basolo , 1996b.…”
Section: Discussionmentioning
confidence: 99%
“…Matyjasiak et al (1999Matyjasiak et al ( , 2000 have shown that experimentally elongated outermost tail feathers impair foraging success in the sand martin and have discussed mechanisms that could potentially explain the initial evolution of size-dimorphic streamers according to the handicap principle. Such a cost could inhibit the evolution of streamers through tail-feather elongation in the sand martin, but it is unlikely to inhibit the development of streamers by evolutionary narrowing of the outermost tail-feather tips without preceding tail elongation in the house martin.…”
Section: Discussionmentioning
confidence: 99%
“…Carpenter et al 1993). Most theoretical and behavioural studies of the role of the avian tail in flight have focused on aerial insectivores, such as swallows ( Norberg 1994;Evans 1998;Matyjasiak et al 1999Matyjasiak et al , 2000Matyjasiak et al , 2004Park et al 2001;Rowe et al 2001). These taxa may be particularly sensitive to small tail-associated changes in body drag, given their high flight speeds maintained over a substantial portion of the day.…”
Section: K1mentioning
confidence: 99%
“…Long tails in birds are thought to degrade flight performance by increasing body drag (Evans & Thomas 1992;Balmford et al 1993;Thomas 1993;Norberg 1995) or by affecting foraging rates and aerial manoeuvrability (Evans 1998;Matyjasiak et al 1999Matyjasiak et al , 2000Matyjasiak et al , 2004Park et al 2000;Rowe et al 2001). For the purposes of quantifying how changes in tail morphology influence drag, the tail has been modelled as an isolated flat plate in free-stream flow (Evans & Thomas 1992;Balmford et al 1993;Thomas 1993;Norberg 1995).…”
Section: Introductionmentioning
confidence: 99%